Silica nanoparticles induce abnormal mitosis and apoptosis via PKC-δ mediated negative signaling pathway in GC-2 cells of mice. (October 2018) - Zhang, Jin; Liu, Jianhui; Ren, Lihua; Wei, Jialiu; Zhang, Feng; Li, Yanbo; Guo, Caixia; Duan, Junchao; Sun, Zhiwei; Zhou, Xianqing
Abstract: The potential health hazards of silica nanoparticles (SiNPs) have attracted more and more attentions. Researches had shown that SiNPs could damage seminiferous epithelium and reduce the quantity and quality of sperms, however the specific mechanism of male reproductive toxicity induced by SiNPs still unclear. So we designed to investigate the mechanism of SiNPs on male mice using spermatocyte lines (GC-2spd cells) after exposure to SiNPs (6.25, 12.5, 25 and 50 μg/mL) for 24 h. The present study showed that SiNPs entered GC-2 cells and mainly localized in the cytoplasm and lysosome. And internalized SiNPs damaged mitochondria structures. As a result, SiNPs not only induced a dose-dependent reduction in cell viability, but also increased the LDH release and apoptosis rate in GC-2 cells. Furthermore, SiNPs induced DNA strand breaks and abnormal mitosis, and arrested GC-2 cells at the G0/G1 phase. Besides, SiNPs could simultaneously activate both PKC-mediated negative signaling pathway (PKC-δ/p53/p21cip1) and positive signaling pathway (PKC-α/MAPK). However, the lower expressions of cyclin E and cyclin-dependent kinases 2 (CDK2) indicated that PKC-δ signaling pathway played a major role in cell cycle process. These results suggested internalized SiNPs in GC-2 cells induced DNA strand breaks and activated PKC-mediated signaling pathway. While the activation of PKC-δ signaling pathway led to cell cycle arrest and apoptosis, thereby resulting in abnormal mitosis. The present study may provide a new evidence to elucidate the toxic mechanisms of male reproductive system, and will be beneficial for safety assessment of SiNPs products. Graphical abstract: Image Highlights: SiNPs could be internalized into the cell cytoplasm and induce cytotoxicity in GC-2 cells. SiNPs could simultaneously activate PKC-δ/p53/p21 cip1 and PKC-α/MAPK signaling pathway. SiNPs induced cell cycle arrest via the activation of PKC-δ signaling pathway, resulting in abnormal mitosis and apoptosis.